STUDY OF GRAPHENE GROWTH BY HWC-VHF-PECVD METHOD USING ANNEALED SILVER FILM CATALYST - ROSHIKIN (NIM:20210024); Pembimbing : Prof. Toto Winata, Ph.D, AHMAD
In this research, graphene growth on the annealed silver thin film by hot wire cell very high frequency plasma enhanced chemical vapour deposition (HWC-PECVD) method was done. Previously, it was prepared catalyst metal thin film by low pressure physical vapour deposition using nickel and silver metal precursor. Nickel metal catalyst was annealed at 600 oC in three conditions annealing time namely 30, 60 and 90 minutes while silver in two conditions 30 and 60 minutes. XRD measurement show that the annealed silver film at 60 minutes has the best structure with maximum intensity located in (111) direction 20 = 38.12o position, interplane distance d = 0.23 nm, lattice parameter a = 0.408 nm and intensity in (111) is 20 times larger than in (222) direction, its mean that structure predominantly by (111) crystal direction, this annealed silver film used for graphene growth catalyst. Furthermore, graphene growth by HWC-VHF-PECVD method using methan (CH4) as precursor with 20 sccm flow rate, 275 oC substrate temperature, 300 mTorr chamber pressure, 70 MHz frequency, time growth for 30 minutes and RF power 20, 10 and 8 watt. Characterization of graphene on silver measured by Raman spectrometer which show that the graphene have some peak at D-1340 cm-1,G-1595 cm-1, G-2647 cm-1 while from UV-Vis measurement show that absorption peak located at(lambada)=411 nm, Raman and SEM image was to show morphology and surface of film.